2022
DOI: 10.3389/fmech.2022.918003
|View full text |Cite
|
Sign up to set email alerts
|

Fast Diesel Aftertreatment Heat-Up Using CDA and an Electrical Heater Between 1.2 and 5.0 kW

Abstract: Commercial vehicles require fast aftertreatment heat-up in order to move the selective catalytic reduction catalyst into the most efficient temperature range to meet upcoming NOX regulations while minimizing CO2. This study is a follow-up study using an electric heater upstream of a LO-SCR followed by a primary aftertreatment system having an engine equipped with cylinder deactivation. The focus of this study is to minimize the maximum power input to the e-heater without compromising tailpipe NOX and CO2. A sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…These were production thermocouples that protrude 2 inches from the wall. This is consistent with other EH works in the past (Matheaus et al, 2021;Zavala et al, 2022). The voltage and current measurements were recorded at the EH and used to calculate the electrical power supplied to it.…”
Section: Electric Heater (Eh) Powersupporting
confidence: 82%
See 4 more Smart Citations
“…These were production thermocouples that protrude 2 inches from the wall. This is consistent with other EH works in the past (Matheaus et al, 2021;Zavala et al, 2022). The voltage and current measurements were recorded at the EH and used to calculate the electrical power supplied to it.…”
Section: Electric Heater (Eh) Powersupporting
confidence: 82%
“…Additional work was performed on this experiment. Zavala et al (Zavala et al, 2022) found that similar excellent NO x control can be achieved with a maximum of 2.4 kW heating power. Reducing the heater power aids in reducing CO 2 since the engine is required to generate the electricity used to power the EH.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations